Trauma Legal en el Teatro Americano del Siglo XX: The crucible de Arthur MillerTrauma Legal en el Teatro Americano del Siglo XX: The crucible de Arthur Miller - Nassima, Brahimi (Revista de Filología Románica, 2017)
Basing on the interdisciplinary approaches of law and literature studies and trauma theory, in particular Felman’s repetitive legal trauma, we advocate that The Crucible demonstrates a past and a modern «legal trauma» in which the judicial hearings and trials of the post-World War II remarkably rehearse the Salem witchcraft trials. We engage with the play’s significant analogy to Communist witch-hunts to show how the justice system, in both periods, proceeds in engendering legal traumas. To prove this claim, we explore the legal narrative and the shared procedures, dramatically leading to accusation and/or execution. We discuss the judiciary’s articulation of law and justice, guilt and innocence within traumatic atmosphere, stressing the point that trauma yields nothing but another trauma, doomed to be repetitive when similar conditions arise. Also, we highlight the role of the play as a universal mode of testimony to Salem’s legal spectre and to any similar hysterical practices.